The Early Asexual Development Regulator fluG Codes for a Putative Bifunctional Enzyme - Iradi-Serrano, Mikel; Tola-García, Leire; Cortese, Marc S.; Ugalde, Unai (Frontiers in Microbiology, 2019)
FluG is a long recognized early regulator of asexual development in Aspergillus nidulans. fluG null mutants show profuse aerial growth and no conidial production. Initial studies reported sequence homology of FluG with a prokaryotic type I glutamine synthetase, but catalytic activity has not been demonstrated. In this study we conducted an in-depth analysis of the FluG sequence, which revealed a single polypeptide containing a putative N-terminal amidohydrolase region linked to a putative C-terminal -glutamyl ligase region. Each region corresponded, separately and completely, to respective single function bacterial enzymes. Separate expression of these regions confirmed that the C-terminal region was essential for asexual development. The N-terminal region alone did not support conidial development, but contributed to increased conidial production under high nutrient availability. Point mutations directed at respective key catalytic residues in each region demonstrated that they were essential for biological function. Moreover, the substitution of the N- and C-terminal regions with homologs from Lactobacillus paracasei and Pseudomonas aeruginosa, respectively maintained functionality, albeit with altered characteristics. Taken together, the results lead us to conclude that FluG is a bifunctional enzyme that participates in an as yet unidentified metabolic or signalling pathway involving a -glutamylated intermediate that contributes to developmental fate.